2019
DOI: 10.3390/w11040866
|View full text |Cite
|
Sign up to set email alerts
|

Impact Assessments of Rainfall–Runoff Characteristics Response Based on Land Use Change via Hydrological Simulation

Abstract: The hydrology response was studied considering the established fact of land use change in Dapoling basin. The whole period was divided into two (1965–1985 and 1986–2012) according to the major land use and land cover change in this region. Xinanjiang model was used to simulate discharge data in the two periods. The hydrologic response to the change could be evaluated by inspecting the response of model parameters and flood elements. The results show that the lag time varied, and the hydrologic elements includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…In these three sub-catchments, the linearity and the stability of DMC (Supplementary Material 2, Figure 8(a)-8(c)-8(e)) indicated that the hydrological processes seemed stable over time and that the variation in specific discharge linearly followed the variation in precipitation. This observation suggested that these three sub-catchments have not experienced significant changes that could influence the precipitationspecific discharge relationship over a short time scale, such as agricultural development, wetland drainage, dam construction, urbanisation, land abandonment, afforestation or deforestation (Mao & Cherkauer 2009;Zhou et al 2019).…”
Section: The Precipitation-specific Discharge Relationshipmentioning
confidence: 94%
“…In these three sub-catchments, the linearity and the stability of DMC (Supplementary Material 2, Figure 8(a)-8(c)-8(e)) indicated that the hydrological processes seemed stable over time and that the variation in specific discharge linearly followed the variation in precipitation. This observation suggested that these three sub-catchments have not experienced significant changes that could influence the precipitationspecific discharge relationship over a short time scale, such as agricultural development, wetland drainage, dam construction, urbanisation, land abandonment, afforestation or deforestation (Mao & Cherkauer 2009;Zhou et al 2019).…”
Section: The Precipitation-specific Discharge Relationshipmentioning
confidence: 94%
“…Determination of T L can give appropriate information on the time of peak flood release from a river basin, which is vital to manage river flooding (Zhou et al, 2019). It could be a comprehensive index associated with various internal hydrological processes in catchments.…”
Section: Introductionmentioning
confidence: 99%
“…Land-use planning and management are crucial factors that influence the sustainability of water resources (Homdee et al, 2011). Changes in land use and management practices can lead to alterations in key hydrological elements, such as evapotranspiration (Liu et al, 2008;Zhou et al, 2019), runoff depth (Sultan et al, 2017(Sultan et al, , 2018a(Sultan et al, , 2018b, mean annual runoff (Ebabu et al, 2018), soil erosion (Fenta et al, 2020(Fenta et al, , 2021, and groundwater quality (Abdulkareem et al, 2019), thereby affecting overall basin hydrology (Abdulkareem et al, 2017(Abdulkareem et al, , 2018Setargie et al, 2021;Zhou et al, 2019). Amini et al (2009) showed that river floods were sensitive to land-use change, but they were essentially dependent on the climate and geomorphologic characteristics of river basins.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under the background of increasingly significant environmental changes, the traditional stable watershed assumption in hydrological simulation is facing challenges, which makes the model parameters, representing the hydrological characteristics of the watershed in the model, no longer hold the fixed assumption and weaken the evaluation ability [2]. Studying the parameter characteristics of the hydrological model of the "Unsteady" watershed and improving the simulation effect of the model in the changing environment can provide technical support for the current and future flood control, drought resistance, water resources planning, and management [3]. For example, studies by many scholars show that since the 1970s, with the trend increase in precipitation in the United States, runoff in most parts of the United States has also shown an obvious increasing trend [4].…”
Section: Introductionmentioning
confidence: 99%